MINAT MEMBACA DAN PENGARUHNYA TERHADAP KONTINUITAS BELAJAR SERTA HASIL BELAJAR PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Syafi’i '; Gimin '; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to fine out how the interest of reading and its influence on the countinuity of learning and learning outcomes on studen of Economic Education Courses FKIP University of Riau. The subject of this research is the student of Economic Education Courses FKIP University of Riau, amounted 72 people, the samples are taken by using the proportional sampling. The data are primary data and secondary data with data collection by using questionnaires and documentation. The technique of analysis data I used is Path Analysis processed through SPSS 16.0 For Windows and Microsoft Excel program. The results of this study indicate that interest in reading and continuity of learning have a significant effect on achievement of learning outcomes. Meaning that the higher interest in reading the countinuity of learning will be higher also and indirectly the learning outcomes will increase. Thus to improvestudent learning outcomes, required a high interest in reading and countinuity of learning is also high.Keywords: Interest in Reading, Continuity of Learning,Learning Outcomes.